Zinc-Doped Boron Phosphide Nanocluster as Efficient Sensor for SO2 - Shahid Hussain; Shahzad Ali Shahid Chatha; Abdullah Ijaz Hussain; Riaz Hussain; Muhammad Yasir Mehboob; Shabbir Muhammad; Zaheer Ahmad; Khurshid Ayub (Journal of Chemistry)
Adsorption of SO2 on pure B12P12 and Zn-doped B12P12 is investigated through density functional theory methods. Zn adsorption on BP delivers four optimized geometries: B-Top, P-top, b64, and ring-enlarged geometry with adsorption energies of −57.12 kJ/mol, −14.50 kJ/mol, −22.94 kJ/mol, and −14.83 kJ/mol, respectively. The adsorption energy of SO2 on pristine boron phosphide is −14.92 kJ/mol. Interaction of SO2 with Zn-doped boron phosphide gives four different geometries with adsorption energies of −69.76 kJ/mol, −9.82 kJ/mol, −104.92 kJ/mol, and −41.87 kJ/mol. Geometric parameters such as dipole moment, QNBO, frontier molecular orbital analysis, PDOS, and global indices of reactivity are performed to visualize the changes in electronic properties of B12P12 after Zn and SO2 adsorption.